Pengaruh Kredibilitas Celebrity Endorser dan Kewajaran Harga Terhadap Niat beli Konsumen Wanita Pada Online Shop Produk Pakaian - Indraswari, Ni Made Mahadewi; Pramudana, Komang Agus Satria (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
Normal 0 false false false EN-US X-NONE X-NONE The purpose of this study was to determine the influence of celebrity endorser credibility is seen from the attraction, confidence, expertise and fairness of the price to the consumer's purchase intention in online women clothing shop products. The study was conducted in the city of Denpasar by taking a sample of 110 respondents using purposive sampling method. Collecting data using a questionnaire instrument with a 5-point Likert scale. Hypothesis testing is performed by multiple linear regression. Based on the results of the study, it was found that the variable attractiveness, confidence, expertise, and price reasonableness positive and significant effect on purchase intention. Based on the results of this study suggested that marketers utilize celebrity endorser credibility, as well as set a reasonable price. Through this strategy the expected consumer purchase intention in online shopping for women's clothing will increase. Persuasive and affective consumer will be easily influenced by the credibility and reasonable pricing for consumers in enhancing their purchasing intentions.
Keywords: credibility, celebrity endorser, price fairness, purchase